2016
DOI: 10.3399/bjgp16x686809
|View full text |Cite
|
Sign up to set email alerts
|

Recent migrants’ perspectives on antibiotic use and prescribing in primary care: a qualitative study

Abstract: BackgroundCurrently there is great interest in antibiotic prescribing practices in the UK, but little is known about the experiences of the increasing numbers of recent migrants (those present in the UK for >1 year but <5 years) registered at GP practices. Qualitative research has suggested that reasons for not prescribing antibiotics may not be clearly communicated to migrants.AimThis study aimed to explore the factors that shape migrants’ experiences of and attitudes to antibiotics, and to suggest ways to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…The concern with over-reliance on paracetamol and perception of reluctance by the GP is not unique to the Eastern European community in the UK. Another UK study about the experiences of GP antibiotic prescribing to recent migrants found participants from Sierra Leone, Sudan, Zimbabwe, Iran and Poland were all frustrated by the GP advising paracetamol [ 36 ]. A study of Somali refugees’ experiences of the Dutch healthcare system [ 37 ] also found the same frustration.…”
Section: Discussionmentioning
confidence: 99%
“…The concern with over-reliance on paracetamol and perception of reluctance by the GP is not unique to the Eastern European community in the UK. Another UK study about the experiences of GP antibiotic prescribing to recent migrants found participants from Sierra Leone, Sudan, Zimbabwe, Iran and Poland were all frustrated by the GP advising paracetamol [ 36 ]. A study of Somali refugees’ experiences of the Dutch healthcare system [ 37 ] also found the same frustration.…”
Section: Discussionmentioning
confidence: 99%
“…When children fall ill, parents strive for the best medicine available [21,33]. In less developed regions, antibiotics are often loosely regulated and erroneously seen as panaceas [34,35]. Perceived experiences of recovery after taking antibiotics for symptoms of viral infections, a phenomenon described as a self-fulfilling prophecy by some clinicians [36], make parents develop their preferences when choosing drugs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous earlier studies have investigated the negative influence of language barriers on patient experience, health literacy and patient–provider relationship 43. Communication was also described as essential for the adoption of new health concepts, for example, the rational use of antibiotics 44. Although the requirement of interpreters is not debated, most healthcare systems in Europe do not have established payment policies for interpreter services.…”
Section: Discussionmentioning
confidence: 99%